Biotechnology and crop improvement - KUMAR, P ANANDA; MOHAPATRA, TRILOCHAN; SHARMA, TILAK R; BHATTACHARYA, RAMCHARAN; DASH, PRASANTA K; GUPTA, NAVIN C; SOLANKE, AMOL KUMAR U (The Indian Journal of Agricultural Sciences, 2011)
Conventional plant breeding is the backbone of agricultural development. It has very significantly contributed in the past to genetic enhancement of crops, particularly for breeding high-yielding crop cultivars. The quantum jump in agricultural productivity which was achieved during late sixties and early seventies needs further enhancement to ensure food and nutritional security of the growing population. Advances in modern biology, especially biotechnology, offer many advantages over traditional techniques of plant breeding. The applications of biotechnology in crop improvement can be broadly grouped into three categories, viz precise isolation and deployment of genes, irrespective of source and target genome, marker-assisted selections and large throughput characterization of genome, transcriptome, proteome or metabolome. The most compelling advantage of plant biotechnology is the ability to transfer foreign genes to confer novel traits. An entire array of traits viz. insect pest and pathogen resistance, abiotic stress tolerance, herbicide tolerance, augmentation of nutritional qualities etc. have been successfully achieved by plant transformation. Another significant application of biotechnology in crop improvement has been ‘marker-assisted selention (MAS). Development and integration of DNA-based molecular markers in the selection process has empowered the breeder to identify desired genotype without any interference of environmental effect of tissue specificity of expression. High throughout genomics emerged as a promising area in crop biotechnology programmes. This is because most of the commercially relevant plant traits are interaction of large number of genes, their positions on chromosomes and promoters controlling them. While structural genomics deals with sequence analysis of total genetic information in an organism, efforts in functional genomics are directed to unravel and understand the mechanism by which this information is used by an organism. Systematic study of complete repertoire of metabolites/chemicals of any organism has given birth to a new area of research ‘metabolomics’. Integration of genomics and proteomics with metabolomics will enrich our understanding to gene-function relationship that can be utilized in achieving crop improvement towards higher productivity.